Apolipoprotein E ϵ4 allele and neuropsychiatric symptoms among older adults in Central Africa (EPIDEMCA study). (15th March 2021) - Yoro-Zohoun, Inès; Houinato, Dismand; Nubukpo, Philippe; Mbelesso, Pascal; Ndamba-Bandzouzi, Bébène; Lambert, Jean-Charles; Clément, Jean-Pierre; Dartigues, Jean-François; Preux, Pierre-Marie; Guerchet, Maëlenn
Abstract: Objectives: To evaluate the association between neuropsychiatric symptoms and apolipoprotein E (APOE) ϵ4 allele among older people in Central African Republic (CAR) and the Republic of Congo (ROC). Design: Multicenter population-based study following a two-phase design. Setting: From 2011 to 2012, rural and urban areas of CAR and ROC. Participants: People aged 65 and over. Measurements: Following screening using the Community Screening Interview for Dementia, participants with low cognitive scores (CSI-D ≤ 24.5) underwent clinical assessment. Dementia diagnosis followed the DSM-IV criteria and Peterson's criteria were considered for Mild Cognitive Impairment (MCI). Neuropsychiatric symptoms were evaluated through the brief version of the Neuropsychiatric Inventory (NPI-Q). Blood samples were taken from all consenting participants before APOE genotyping was performed by polymerase chain reaction (PCR). Logistic regression models were used to evaluate the association between the APOE ϵ4 allele and neuropsychiatric symptoms. Results: Overall, 322 participants had complete information on both neuropsychiatric symptoms and APOE status. Median age was 75.0 years and 81.1% were female. Neuropsychiatric symptoms were reported by 192 participants (59.8%) and at least 1 APOE ϵ4 allele was present in 135 (41.9%). APOE ϵ4 allele was not significantly associated with neuropsychiatric symptoms but showed a trend toward a protective effect in some models. Conclusion: This study is the first one investigating the association between APOE ϵ4 and neuropsychiatric symptoms among older people in sub-Saharan Africa (SSA). Preliminary findings indicate that the APOE ϵ4 allele was not associated with neuropsychiatric symptoms. Further research seems, however, needed to investigate the protective trend found in this study.